Web-Based Conference Management pada The International Conference on Computer Science and Technology (WeBEST) - Listyorini, Tri; Cahyo Wibowo, Budi; Dahlan, Mohammad; Tauhida, Dina; Rahmawati, Ratri (Journal of Science and Education (JSE), 2024)
The International Conference on Computer Science and Technology (ICCSET) is an annual routine agenda by the Faculty of Engineering, Universitas Muria Kudus. The usefulness of this agenda adds to the publications of UMK Engineering faculty lecturers in particular and other universities in general. The consistency of the Faculty of Engineering in holding ICCSET attracts researchers from outside UMK. The obstacle that arises during ICCSET is the ICCSET data management system. The system uses Google Forms, where Google Forms have not been integrated between forms. This makes the ICCSET data processing system difficult due to incomplete data. This research resulted in a web-based management system for ICCSET at the Faculty of Engineering, Universitas Muria Kudus, which was named WeBEST - Web-Based Conference Management at The International Conference on Computer Science and Technology (ICCSET)